Human rights in India - "Sehgal, B. P. Singh (ed.)" (New Delhi, 1995)
This book deals with contributed papers presented at Seminar on Human Rights--Global Problems and Perspectives held in March 1995 at University of Jammu.
Keywords: Civil rights - India